Molecular and clinical analysis of Chinese patients with anaplastic lymphoma kinase (ALK)‐rearranged non‐small cell lung cancer. Issue 10 (23rd September 2019) - Zhou, Xiaoyun; Shou, Jiawei; Sheng, Jin; Xu, Chunwei; Ren, Shengxiang; Cai, Xiuyu; Chu, Qian; Wang, Wenxian; Zhen, Qinhong; Zhou, Yuefen; Li, Wenfeng; Pan, Hong; et al.
Abstract: Anaplastic lymphoma kinase ( ALK ) fusions have been recognized as a therapeutic target in non‐small cell lung cancer (NSCLC). However, molecular signatures and clinical characteristics of the Chinese population with ALK ‐rearranged NSCLC are not well elucidated. In the present study, we carried out targeted next‐generation sequencing on tissue and plasma ctDNA samples in 1688 patients with NSCLC. Overall, ALK fusions were detected in 70 patients (4.1%), and the frequencies of ALK fusions detected in tissue and plasma samples were 5.1% and 3.3%, respectively. Additionally, the prevalence of breakpoint locations for EML4‐ALK fusions in ctDNA was significantly correlated with that in tumor tissues ( R 2  = .91, P  = .045). According to age, the incidence rates of ALK fusions among young (age <45 years), middle‐aged (between 45 and 70 years) and elderly (>70 years) patients were significantly different ( P  < .001). In 70 ALK ‐rearranged cases, coexistence of epidermal growth factor receptor ( EGFR ) alterations and ALK fusions was detected in 12 cases (17.1%) and EGFR mutations tended to coexist with non‐ EML4‐ALK rearrangements. Notably, novel ALK fusion partners, including TRIM66, SWAP70, WNK3, ERC1, TCF12 and FBN1 were identified in the present study. Among EML4 ‐ ALK fusion variants, patients with variant V1 were younger than patients with variant V3 ( P  = .023), and TP53 mutations were more frequently concurrent with variant V3 compared with variant V1 ( P  = .009). In conclusion, these findings provide new insights into the molecular‐clinical profiles of patients with ALK ‐rearranged NSCLC that may improve the treatment strategy of this population. Abstract : This study simultaneously investigated the prevalence of ALK rearrangements in tissue and plasma samples from a large cohort of patients with NSCLC, showing the significance of detection of ALK fusions by ctDNA‐based NGS. Identification of novel ALK fusion partners, coexistence between ALK fusions and variants of other oncogenic drivers, and characterization of EML4‐ALK‐positive patients support the critical use of molecular profiling by NGS in NSCLC.